Note: You are looking at a static copy of the former PineWiki site, used for class notes by James Aspnes from 2003 to 2012. Many mathematical formulas are broken, and there are likely to be other bugs as well. These will most likely not be fixed. You may be able to find more up-to-date versions of some of these notes at http://www.cs.yale.edu/homes/aspnes/#classes.

# 1. Surjectivity

Let f:A→B. Prove that f is surjective if and only if, for all sets C and functions g,h:B→C, g∘f = h∘f implies g = h.

## 1.1. Solution

Suppose first that f is surjective. Fix C, g, and h and suppose that g≠h. Then there exists some x in B such that g(x)≠h(x). Because f is surjective, there is some y in A such that f(y) = x. But then (g∘f)(y) = g(f(y)) = g(x) ≠ h(x) = h(f(y)) = (h∘f)(y). It follows that g∘f ≠ h∘f. By contraposition we have that if f is surjective, then g∘f = h∘f implies g = h.

Alternatively, suppose that f is not surjective. Then there is some x in B such that f(y)≠x for all y in A. Let C = {0,1} and define the functions g(z) = 1 for all z in B and h(z) = 1 if z≠x, h(z) = 0 if z=x. Now for any y in A, we have (g∘f)(y) = g(f(y)) = 1 and (h∘f)(y) = h(f(y)) = 1 (because f(y) can't equal x). But g≠h because they disagree on x. So we have demonstrated that if f is not surjective, then it is not the case that for all C, g, h, g∘f = h∘f implies g = h.

# 2. A recursively-defined function

Let f:ℕ→ℤ be defined by the rule:

• f(0) = a
• f(1) = b
• For n > 1, f(n) = 2f(n-1) - f(n-2)

where a,b∈ℤ.

Show that there exist constants c and d (which may depend on a and b but not on n), such that f(n) = cn+d for all n∈ℕ.

## 2.1. Solution

First let's find c and d and then show (by induction) that they work.

Look at f(0) and f(1), we have

• c⋅0+d = a
• c⋅1+d = b

The first case gives us d = a; the second gives us b = c + d = c + a or c = b - a. So our formula for f is f(n) = (b-a)n + a. Now we'll show that this works.

Base case: f(0) = (b-a)⋅0 + a = a, f(1) = (b-a)⋅1 + a = b.

Induction step: Let n > 1, compute f(n) = 2f(n-1) - f(n-2) = 2((b-a)(n-1)+a) - ((b-a)(n-2)+a) = (b-a)(2(n-1)-(n-2)) + a(2-1) = (b-a)(2n-2+n+2) + a = (b-a)n + a. Note the second step uses the (strong) induction hypothesis that f(n') = (b-a)n' + a for all n' ≤ n-1.

# 3. Sums of products

Prove that the following identity holds for all n∈ℕ:

## 3.1. Solution

The proof is by induction on n. The base case is n=0; here the left-hand side is 1 + 0 (since the sum is empty), while the right-hand side is 1 (since the product is empty).

For n > 0, we have

Here step (2) uses the induction hypothesis.

2014-06-17 11:57